Discrete dislocation dynamics study on cutting behavyior of dislocation around rafted structure in nickel-based superalloys [electronic resource] - Mohammad Iman Ramlan. 1991-; Joy Rizki Pangestu Djuansjah, superviso; Fakulti Kejuruteraan Mekanikal (2014)
Project Paper (Sarjana Muda Kejuruteraan (Mekanikal - Pembuatan)) -- Universiti Teknologi Malaysia, 2014